Accuracy of the saxton-rawls method for estimating the soil water characteristics for mineral soils of Malaysia - Teh, Christopher Boon Sung; Iba, Jane (Universiti Putra Malaysia Press, 2010)
The purpose of this study was to determine the accuracy of the Saxton-Rawls method in estimating the soil water characteristics of a wide range of mineral soils of Malaysia. This study found that it was necessary to calibrate the Saxton-Rawls method for the soils of Malaysia. The developed equation for calibration was Pti = a $ Pi ]1 - Pig, where Pi and Pi t are the uncalibrated and calibrated estimated values, respectively, for the soil sample no. i, and the parameter values of a were 2.225, 1.605, and 1.528 (for saturation, field capacity, and permanent wilting point) respectively. The calibrated method was validated against three independent soil data sets. The validation tests showed that the calibrated method remained stable and was more accurate than that without any calibration, by an average between 8 to 49%.